Recent advances in epicutaneous immunotherapy and potential applications in food allergy - Hervé, Pierre-Louis; Dioszeghy, Vincent; Matthews, Katie; Bee, Katharine J.; Campbell, Dianne E.; Sampson, Hugh A. (Frontiers in Allergy, 2023)
Given the potent immunological properties of the skin, epicutaneous immunotherapy (EPIT) emerges as a promising treatment approach for inducing immune tolerance, particularly for food allergies. Targeting the highly immunocompetent, non-vascularized epidermis allows for the application of microgram amounts of allergen while significantly reducing the risk of allergen passage into the bloodstream, thus limiting systemic allergen exposure and distribution. This makes EPIT highly suitable for the treatment of potentially life-threatening allergies such as food allergies. Multiple approaches to EPIT are currently under investigation for the treatment of food allergy, and these include the use of allergen-coated microneedles, application of allergen on the skin pretreated by tape stripping, abrasion or laser-mediated microperforation, or the application of allergen on the intact skin using an occlusive epicutaneous system. To date, the most clinically advanced approach to EPIT is the Viaskin technology platform. Viaskin is an occlusive epicutaneous system (patch) containing dried native allergen extracts, without adjuvants, which relies on frequent application for the progressive passage of small amounts of allergen to the epidermis through occlusion of the intact skin. Numerous preclinical studies of Viaskin have demonstrated that this particular approach to EPIT can induce potent and long-lasting T-regulatory cells with broad homing capabilities, which can exert their suppressive effects in multiple organs and ameliorate immune responses from different routes of allergen exposure. Clinical trials of the Viaskin patch have studied the efficacy and safety for the treatment of life-threatening allergies in younger patients, at an age when allergic diseases start to occur. Moreover, this treatment approach is designed to provide a non-invasive therapy with no restrictions on daily activities. Taken together, the preclinical and clinical data on the use of EPIT support the continued investigation of this therapeutic approach to provide improved treatment options for patients with allergic disorders in the near future.